Desire Thinking across addictive behaviours: A systematic review and meta-analysis. (November 2019) - Mansueto, Giovanni; Martino, Francesca; Palmieri, Sara; Scaini, Simona; Ruggiero, Giovanni Maria; Sassaroli, Sandra; Caselli, Gabriele
Abstract: Introduction: Desire Thinking (DT) is a voluntary cognitive process aimed at orienting to prefigure images, information, and memories about positive target-related experience. It comprises of two components: Imaginal Prefiguration and the Verbal Perseveration. DT has been found to be positively associated with alcohol use, gambling, nicotine use, and problematic Internet use. Despite this, neither qualitative nor quantitative reviews have been undertaken to critically summarize findings about the association between DT and addictive behaviours. The aim of this systematic review and meta-analysis is to evaluate the strength of the association between DT and addictive behaviours. Method: In accordance to PRISMA criteria, a research was conducted on PubMed and PsycInfo. A manual search of reference lists was also run. Search terms were: "addiction / gambling / alcohol / tobacco / nicotine / drug / cocaine / marijuana / cannabis / opioid / heroin / methadone / internet" AND "Desire Thinking". Results: Ten studies were included. Both components of DT were found to be associated with addictive behaviours (alcohol use, nicotine use, gambling, problematic Internet use) in both clinical and community samples. The strength of the association between Verbal Perseveration and addictive behaviours appears to be stronger for alcohol and nicotine use than Internet use. The association between DT and addictive behaviours is not moderated by age. Conclusion: DT is present across different addictive behaviours. The assessment of DT and tailored interventions aimed to reduce the propensity to engage in DT should be considered in the treatment of addictive behaviours. Highlights: Desire Thinking is associated with different addictive behaviours Imaginal Prefiguration is associated with different addictive behaviours Verbal Perseveration is more related with substance than to non-substance addiction Desire Thinking might be a therapeutic target for the treatment of addictions